The good friday agreement's impact on political cooperation: A review - David Mitchell; Etain Tannam; Sarah Wallace (Trinity College Dublin, The University of Dublin, Trinity Research in Social Sciences (TRiSS), 2018)
This article aims to examine the impact of the Good Friday Agreement on political cooperation. It examines party political cooperation in Northern Ireland and also bilateral British-Irish intergovernmental cooperation. In the first section,theAgreement's consociational system and its criticismsare outlined. In section two, the effect of the Agreement on cooperation between the Northern Ireland political partiesis assessed. In section three, the impact on British-Irish East-West cooperation is assessed along with the effects of Brexit. In conclusion, it is argued that Strand Three of the Good Friday Agreement, providing for the institutionalisation of intergovernmental cooperation was not implemented adequately and this weakness has been exposed by Brexit.
Keywords: 330; Good Friday Agreement; Brexit; political cooperation; intergovernmental cooperation; British-Irish Intergovernmental Conference